2014
DOI: 10.1016/j.jpsychores.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Attachment anxiety predicts IL-6 and length of hospital stay in coronary artery bypass graft surgery (CABG) patients

Abstract: ObjectiveThe mechanisms underlying the association between adult attachment and health are not well understood. In the current study, we investigated the relationship between attachment anxiety, attachment avoidance, inflammation, and length of hospital stay in coronary artery bypass graft (CABG) surgery patients.Method167 CABG patients completed an attachment questionnaire prior to surgery, and blood samples were taken before and after surgery to assess inflammatory activity.ResultsWe found that attachment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Our group has previously demonstrated that depression and attachment anxiety are associated with length of hospital stay and increased levels of inflammation after CABG surgery. Depression was associated with increased levels of C‐reactive protein and longer hospital stay while attachment anxiety, but not attachment avoidance, predicted higher levels of interleukin‐6, greater sleep disturbance, and longer hospital stay following CABG surgery (Kidd et al ., ; Poole, Kidd et al ., ; Poole, Leigh et al ., ). The current study expands on our existing work and the wider literature by providing evidence that supports attachment as a framework for understanding the aetiology and presentation of depression and anxiety symptomatology in CABG patients, which may have implications for recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously demonstrated that depression and attachment anxiety are associated with length of hospital stay and increased levels of inflammation after CABG surgery. Depression was associated with increased levels of C‐reactive protein and longer hospital stay while attachment anxiety, but not attachment avoidance, predicted higher levels of interleukin‐6, greater sleep disturbance, and longer hospital stay following CABG surgery (Kidd et al ., ; Poole, Kidd et al ., ; Poole, Leigh et al ., ). The current study expands on our existing work and the wider literature by providing evidence that supports attachment as a framework for understanding the aetiology and presentation of depression and anxiety symptomatology in CABG patients, which may have implications for recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of cortisol, in turn, is associated with alterations in the immune system. Recent work has linked attachment anxiety with indicators of weaker immune functioning, including lower T-cell counts (involved in activating immune cells and responding to infections) (Jaremka, et al, 2013), higher levels of latent herpesvirus reactivation (Fagundes, et al, 2014), and exacerbated inflammatory response to cardiac surgery (Kidd, et al, 2014), suggesting that failures to perceive one’s partner as responsive may lead to impairments in the immune system.…”
Section: Partner Responsiveness Attachment and Healthmentioning
confidence: 99%
“…Other work further supports a link between anxious attachment and poorer immune function: Anxiously attached husbands and wives evidenced fewer T-cells over two days (together with higher cortisol levels) [30], and anxiously attached individuals showed elevated antibody titers to the Epstein-Barr virus on two tests one year apart [52]. Similarly, another recent study of adults (most males) found that individuals who were higher in attachment anxiety (but not those higher in avoidance) showed a greater increase in an inflammation marker (Il-6) after cardiac surgery [53]. (Attachment was unrelated to two other inflammation markers: TNF alpha and CRP.)…”
Section: Immune Responsesmentioning
confidence: 99%